ANALYSIS OF MACRO ECONOMIC INDICATORS AND THEIR INFLUENCE ON STOCK INDEXES IN INDONESIA - Asih, Dinda Fadila; Inayah, Fitri Dwi; Ardini, Nabila; Husna, Nurhidayati; Guntari, Pinasti Sri; Dipa, Mira (Proceeding International Seminar of Islamic Studies, 2024)
The inflation variable has a good influence on the Indonesian Sharia Stock Index (ISSI) both in the short and long term. The aim is to find out what happens if inflation occurs due to excess demand compared to the existing supply. This article uses secondary data which collects data sourced from journals and information obtained from various data analyzes taken from the internet. The results of this research are (1) the large influence of foreign capital which will enter the financial markets in developing countries. (2) In the IHSG an investor can see what is happening in the market, whether there is an increase or decrease, to find out the investor's strategic targets. (3) Investors will experience losses if the deposit interest rate will reduce the profits they can get if they invest in the form of deposits. Where the results of our article can provide information about macroeconomic indicators and their influence on stock indices in Indonesia.